Comparative Genomic Sequence Analysis of the Human Chromosome 21 Down Syndrome Critical Region - Toyoda, Atsushi; Noguchi, Hideki; Taylor, Todd D.; Ito, Takehiko; Pletcher, Mathew T.; Sakaki, Yoshiyuki; Reeves, Roger H.; Hattori, Masahira

(untitled) (Genome Research, 2002)
Comprehensive knowledge of the gene content of human chromosome 21 (HSA21) is essential for understanding the etiology of Down syndrome (DS). Here we report the largest comparison of finished mouse and human sequence to date for a 1.35-Mb region of mouse chromosome 16 (MMU16) that corresponds to human chromosome 21q22.2. This includes a portion of the commonly described “DS critical region,” thought to contain a gene or genes whose dosage imbalance contributes to a number of phenotypes associated with DS. We used comparative sequence analysis to construct a DNA feature map of this region that includes all known genes, plus 144 conserved sequences ≥100 bp long that show ≥80% identity between mouse and human but do not match known exons. Twenty of these have matches to expressed sequence tag and cDNA databases, indicating that they may be transcribed sequences from chromosome 21. Eight putative CpG islands are found at conserved positions. Models for two human genes, DSCR4 and DSCR8, are not supported by conserved sequence, and close examination indicates that low-level transcripts from these loci are unlikely to encode proteins. Gene prediction programs give different results when used to analyze the well-conserved regions between mouse and human sequences. Our findings have implications for evolution and for modeling the genetic basis of DS in mice.[Sequence data described in this paper have been submitted to the DDBJ/GenBank under accession nos. AP003148through AP003158, and AB066227. Supplemental material is available athttp://www.genome.org.]